Beneficial alteration of blood biochemical parameters by Telmisartan-Pioglitazone combination in rat - Ibrahim, Fuzianna; Sengupta, Pinaki; Das, Arindam (2016)
Background: It is very rare nowadays that type-2 diabetes mellitus patient is not having mild to moderate level of hypertension. In spite of having best medical therapies to control blood glucose level, diabetic patients suffer from poorer cardiovascular outcomes than nondiabetic individuals. Although the primary component of diabetes care is to control blood glucose level, management of cardiovascular risk factors should also be considered as vital one. Hence, concurrent administration of antihypertensive medication is almost essential for proper management of diabetes in an appropriate antidiabetic drug regimen. Objective: The safety profile of drugs may get altered when they are combined together. The potential drug interactions should be studied well and documented properly before proceeding for their co-administration. The aim of this study was to investigate the effect of combining telmisartan with pioglitazone on blood biochemistry after simultaneous oral administration in rat. Methods: Profiling of blood biochemical parameters of the combination was assessed. Pioglitazone and telmisartan were administered orally at daily doses (low, medium and high dose levels) alone and in combination to rats for 28-days. The rat blood for clinical chemistry was collected, allowed to clot, centrifuged and serum was collected. Serum levels of total protein, blood urea, serum glutamate pyruvate transaminase (SGPT) and serum glutamate oxaloacetate transaminase (SGOT) were estimated by an automated bioanalyzer. Results: Treatment with pioglitazone showed to decrease the total protein, urea, SGPT and SGOT level whereas telmisartan treated rats exhibited increased serum concentration of urea, SGPT and SGOT. Interestingly, when they were co- administered, the inhibitory effect of pioglitazone on serum level of urea, SGPT and SGOT were nullifies and the serum concentration of these parameters were showed to be almost similar to the control group. Thisalteration in biochemical parameters confirms the beneficial effect of this combination treatment on the liver and kidney function. Conclusion: There were no harmful changes found in the level of SGPT and SGOT in serum of pioglitazone-telmisartan treated group which confirms lacking in hepatotoxic potential of the combination. The combination treatment showed no detrimental effects on kidney as no significant differences were observed on urea and total protein concentrations in blood. Co-administration of telmisartan with pioglitazone showed to have beneficial effect in terms of alteration of the biochemical parameters in rats. This repeated dose short term interaction study suggests that the combination can be taken into account for further study for its applicability to use as a combination therapy for diabetic hypertensive patients.